Is ectopic Cushing’s syndrome underdiagnosed in patients with small cell lung cancer? - Piasecka, Marta; Larsson, Martin; Papakokkinou, Eleni; Olsson, Lena; Ragnarsson, Oskar (Frontiers in Medicine, 2022)
Introduction Ectopic Cushing’s syndrome (ECS) is an uncommon disorder. Recently, however, a larger proportion of patients with endogenous Cushing’s syndrome (CS) had ECS than has previously been reported. Objective The aim of this study was to determine whether ECS is an underdiagnosed disorder in patients with small-cell lung cancer (SCLC). Materials and methods Medical records from consecutive patients diagnosed with SCLC at our hospital between 2013 and 2019 were reviewed (N = 213; mean age 69.5 ± 9 years; range, 36–89 years). The probability of having ECS was evaluated by review of biochemical and clinical features, including presence of recent onset diabetes mellitus, therapy resistant hypertension and/or spontaneous hypokalaemia. Results Of 213 identified patients with SCLC, one (0.5%) patient had confirmed ECS, two (1%) patients had probable ECS, and twenty-three (11%) patients had possibly ECS. Patients with SCLC and possibly or probable ECS exhibited a significantly shorter survival than patients only with SCLC (8 vs. 14 months, respectively). Conclusions Our findings indicate that ECS is underdiagnosed in patients with SCLC. Given the serious consequences of untreated ECS, the low detection rate highlights the need to improve endocrine work-up of patients with SCLC who present with biochemical and clinical features associated with ECS. Prospective studies are needed to establish a reliable assessment of the incidence of ECS and to optimise early detection strategies.